Species diversity and threats on the habitat of Vatica javanica in the Ciangir Forest, Indonesia. Issue 1 (August 2020) - Fambayun, R A; Kalima, T; Rachmat, H H
Abstract: Vatica javanica is one of the endemic dipterocarp species in Java. It is highly prioritized to be conserved and categorized as critically endangered A1cd, D ver 2.3 based on International Union for Conservation of Nature red list. There is still a lack of ecological study related to this Javan endemic dipterocarp. At the national level, V. javanica is categorized as critical EN A2cd; B2ab (ii, iii) ver.4.0. Information on the current population condition is essential to support the baseline data for the conservation effort of the species. To investigate the species diversity and threats in V. javanica' s natural habitat, we established 26 transects of 20m x 50m based on the V. javanica' occurrence and identified all the plant species (d = >1cm) composed V. javanica' s population. V. javanica was only found at four out of 26 transects in the Ciangir forest, Kuningan District, West Java, Indonesia. The result showed that the species diversity in this population was very high, Simpson diversity index (α) = 0.96. Furthermore, based on the result of the critical value index (IVI), the population was dominated by V. javanica (20.97), Ficus sp. (11.01), Eurya acuminata (11.01), Dillenia obovata (10.72), and Lithocarpus sundaicus (10.31). This study identified that natural (landslides) and human intervention (land conversion) as the major threats for the species.